Incidence of bacterial vaginosis in patients with idiopathic preterm labour - ., Bijeta; Singh, Shreshtha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objectives of this study were to find the incidence of bacterial vaginosis in patients with idiopathic preterm labour and to assess maternal and fetal outcome. Methods: The study was carried out in the department of Obstetrics and Gynaecology, Patna Medical College, Patna from September 2011 to September 2013.Study was done in 100 pregnant women. 50 patients were cases and 50 were control. Cases were patients admitted with idiopathic preterm labour and controls were patients admitted with term pregnancy. A thorough general, systemic and obstetrical examination was done. Speculum examination was done to exclude leaking and to note the type of discharge which was collected for the pH estimation, amine testing and for making a smear for gram staining. Diagnosis of bacterial vaginosis was confirmed on the basis of Nugent criteria. Maternal and fetal outcome was assessed. Results: The incidence of bacterial vaginosis in patients with idiopathic preterm labour was 30 percent. Bacterial vaginosis was significantly (P <0.05) associated with idiopathic preterm labour. Out of 15 patients who had bacterial vaginosis, 13 had preterm delivery (<37 weeks). In 35 patients without bacterial vaginosis 21 had preterm delivery. Bacterial vaginosis was significantly associated with low birth weight babies (P <0.05). Bacterial vaginosis was significantly associated with neonatal jaundice and neonatal sepsis. Conclusions: Bacterial vaginosis is strongly associated with preterm labour and delivery as well as adversely affects neonatal outcome. Thus screening for bacterial vaginosis in all pregnant women complaining of vaginal discharge and also in all patients with preterm labour is justifiable.